The significance of social exchange theory on the internal performance of the Malaysian Search and Rescue (SAR) teams - Ahmad Zawawi, Azlyn; Ab Halim, Norsyazwani; Kamarunzaman, Nur Zafifa; Ahmad Zawawi, Azita; Halim, Fatimah Wati (Human Resource Management Academic Research Society, 2022)
The social exchange theory (SET) is a social form of exchange that includes tangible or intangible, material or nonmaterial goods between individuals with other individuals. The social exchange involves actions that relate to reward reactions from others. In short, social costs and rewards affect human decisions and behavior. In this paper, SET highlights the reciprocal relationship between the internal factors of Search and Rescue (SAR) team performance, which are team communication, team leadership, and team time management. The essential belief of SET is that individuals in the team enter into and maintain the relationship with the expectation to gain a net positive value. This study involved 209 SAR teams from Peninsular Malaysia. Data were collected using the survey method. Respondents’ demographics and descriptive data such as percentages and frequencies were analyzed using the Statistical Package for Social Sciences (SPSS) Version 26 software for Windows. For deeper analysis and hypothesis testing, data were analyzed using the Structural Equation Modelling (SEM) technique using partial least square analysis by SmartPLS. Analysis revealed that only team communication and team time management were found to be significantly related to SAR team performance. Discussions are provided at the end of this paper to justify the finding.